Fetal megacystis: Institutional experience and outcomes. (12th July 2017) - Taghavi, Kiarash; Sharpe, Caitlin; Stringer, Mark D.; Zuccollo, Jane; Marlow, Jay
Abstract : Background: Fetal megacystis is a sonographic feature that may be indicative of several underlying pathologies. Despite advances in diagnosis and management, the overall prognosis of affected fetuses remains poor and about 50% of such pregnancies are terminated. Aims: To define the frequency, management, survival and renal outcomes of fetal megacystis over nine years at Wellington Hospital, New Zealand. Materials and Methods: A nine‐year retrospective review of fetuses with an antenatal diagnosis of megacystis was undertaken. Results: Sixteen cases were identified (nine live births, five terminations and two perinatal deaths). This gives an observed frequency of one per 940 fetuses scanned. Two‐thirds of the live births have survived and been followed for a mean of 5.3 years. None have required renal dialysis or transplantation to date. Conclusions: The current series contributes to our knowledge of fetal megacystis and helps to inform antenatal counselling. Improved prognostic criteria are urgently required to accurately differentiate between fetuses with favourable versus poor outcomes.